2014
DOI: 10.1037/a0036110
|View full text |Cite
|
Sign up to set email alerts
|

The role of teachers in bullying: The relation between antibullying attitudes, efficacy, and efforts to reduce bullying.

Abstract: In order to battle bullying, it can be important for students to have teachers whom they see as taking an active stand against bullying in terms of propagating antibullying norms and having an efficacious approach to decreasing bullying. This expectation was tested with data from the control schools of the Finnish evaluation of the KiVa antibullying program. Multilevel analyses of data from 2,776 fourth-to sixth-graders showed that students' perceptions of their teachers' efficacy in decreasing bullying was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
146
1
18

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(181 citation statements)
references
References 48 publications
5
146
1
18
Order By: Relevance
“…In contrast to them, ISTs with high self-efficacy tend to differentiate between the various strategies to cope with problem behaviors and change their goals according to students' needs and expectations (Zee and Koomen, 2016). When IST's self-efficacy is high, the students, too, perceive teachers as highly effective in combating bullying (Veenstra et al, 2014). Conversely, teachers with a low self-efficacy are perceived by students as less able to prevent bullying (Crothers and Kolbert, 2004).…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…In contrast to them, ISTs with high self-efficacy tend to differentiate between the various strategies to cope with problem behaviors and change their goals according to students' needs and expectations (Zee and Koomen, 2016). When IST's self-efficacy is high, the students, too, perceive teachers as highly effective in combating bullying (Veenstra et al, 2014). Conversely, teachers with a low self-efficacy are perceived by students as less able to prevent bullying (Crothers and Kolbert, 2004).…”
mentioning
confidence: 86%
“…Furthermore, teachers' self-efficacy correlates negatively with stress and burnout and positively with job satisfaction and commitment (Aloe et al, 2014;Zee and Koomen, 2016). Veenstra et al (2014) showed that teachers' self-efficacy has a strong correlation with teachers' intervention against bullying; classes where teachers had high self-efficacy also had lower occurrences of bullying.A different, but related, notion is that of OEs, defined as an agent's beliefs about the likely consequences of a specific action and the chances that a specific outcome will actually follow from his or her successfully performed behavior (Bandura, 1997;Denzine et al, 2005;Williams et al, 2005). Teachers' expectations about their students' positive outcomes affect how they themselves behave and interact with the students in the classroom (Skinner et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sin embargo, la escuela debería ser la primera en dar el paso, especialmente cuando los efectos de este escaso diálogo se manifiestan en violencia concreta al interior de los centros escolares, sin incluir los efectos de la llamada violencia simbólica (Bourdiue, 1987). En este sentido, el rol del docente es fundamental como agente de intervención y prevención de aquellas conductas violentas (Demaray et al, 2013;Veenstra et al, 2014;Bradshaw et al, 2013;Guimond et al, 2015).…”
Section: El Diálogo Como Fundamento Democrático En La Escuelaunclassified
“…of the faculty, staff, administration, and students. 59 Chillingly, one of the key factors that reinforces bullying is the presence of children who are bystanders. Do they help, jeer, idly observe, or otherwise fail to intervene?…”
Section: Are Hierarchies and Their Negative Social Effects Inevitable?mentioning
confidence: 99%